A practitioner's guide to public relations research, measurement and evaluation - Stacks, Don W.; Michaelson, David; IG Publishing (New York, N.Y. Business Expert Press, 2010)
This volume introduces the reader to the world of research and public relations research in particular. It takes a best practices approach--one that focuses on taking the appropriate method and rigorously applying that method to collect the data that best answer the objectives of the research. It also presents an approach to public relations that focuses on establishing the profession's impact on the client's return on investment in the public relations function, whether that function be aimed at internal or external audiences. By the end of the book, the reader will not be a research expert but will understand why and how research is conducted. Further, the reader will be able to apply best practice standards to any research done by supply side vendors or internal research departments.
Contemporary public relations practice has developed over the last several decades from the weak third sister in marketing, advertising, and public relations mix to a full player. Part of that development can be traced to a change in the way that public relations is researched, measured, and evaluated. Both Drs. Stacks and Michaelson are members of that Commission and have been in the forefront of taking public relations research, measurement, and evaluation to the next level. This book will provide the business reader with the necessary understanding of the problems and promises of public relations research, measurement, and evaluation and the public relations practitioner as guide to effective use of methods, measures, and evaluation in providing grounded evidence of the success (or failure) of public relations campaigns.
Part I. Introduction to public relations research, measurement, and evaluation -- Chapter 1. Introduction to research and evaluation in public relations -- Chapter 2. The business of public relations -- Chapter 3. Measuring public relations outcomes -- Part II. Qualitative methods for effective public relations research, measurement, and evaluation -- Chapter 4. Secondary research -- Chapter 5. Qualitative research methodologies -- Chapter 6. Content analysis -- Part III. Quantitative methods for effective public relations research, measurement, and evaluation -- Chapter 7. Survey methodology -- Chapter 8. Statistical analysis -- Chapter 9. Sampling -- Part IV. Wrapping up -- Chapter 10. Best practices in public relations research, measurement, and evaluation -- Appendix. Dictionary of public relations, measurement and research -- Notes -- References -- Index.
Electronic reproduction.
Keywords: Public relations -- Research; Electronic books